STUDI WARNA DAN GAYA PADA KARYA YAZID - Miswar Miswar; Rica Rian; Yunis Muler; Rajudin Rajudin (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2022)
This study reveals the characteristics of color and style in Yazid's work. The method used in this study refers to a qualitative research methodology that includes observations, interviews, and the use of documents in the field. In addition, this study uses qualitative methods, which include interviews, field notes, photos, videos, personal documents, and others. Yazid's painting takes the theme of the exotic nature of West Sumatra, which leads to Mooi Indie's work. Yazid's paintings are exciting in terms of the colors presented. The colors in Yazid's work are soft and light, and rarely in his work are their colors that are too dark. The brightness of his paintings is also low; some of his works use bright colors. The color composition in the work is very well made. No colors can damage each other, so a harmonious and mutually supportive color arrangement is achieved. In tracing Yazid's paintings, they are classified into four styles according to Feldman, the first is the objective accuracy style, the second is formal arrangement style, the third is expressive style, and the fourth is the fantasy style. The presence of Yazid's work greatly influenced the development of naturalist-style painting in West Sumatra, considering that Yazid is a senior artist who devoted his life to painting. Keywords: Yazid's painting, color, style. AbstrakPenelitian ini mengungkap karakteristik warna dan gaya pada karya Yazid. Dalam konteks penelitian ini, istilah